Extraskeletal Tc-99m MDP uptake Accumulation in a calcified Uterine Leiomyoma: A benign mimic on Bone scan - Fatima Yousaf; Iman Tahir; Aamna Hassan (Journal of the Pakistan Medical Association, 2025)
Bone scintigraphy is primarily used for the assessment of osseous structures, soft tissue uptake of Tc-99m Methylene deoxy- phosphonate (MDP) is unusual in normal circumstances and may lead to unsuspected diagnosis. We present a case highlighting the importance of studying the soft tissues to assess for findings other than osseous on bone scintigraphy in a patient with prior history of breast carcinoma. Keywords: Breast cancer, calcified uterine fibroid, Tc-99m MDP bone scan